Bimodal inguinal sentinel lymph node imaging using a radiation-free fluorescent magnetic hybrid tracer in penile cancer patients - Michalik, Bianca; Engels, Svenja; Otterbach, Maximilian C.; Maurer, Martin H.; Wawroschek, Friedhelm; Winter, Alexander (Frontiers in Oncology, 2025)
Invasive lymph node (LN) staging is crucial for survival in penile cancer (PeCa) patients. To lower patient morbidity associated with radical inguinal lymphadenectomy, sentinel node biopsy (SNB) is recommended. Application of conventional radioactive/fluorescent tracers for sentinel node (SN) labelling is limited to centers with nuclear medicine or lacks pre-operative imaging. We introduce a radiation-free fluorescent magnetic hybrid tracer for bimodal inguinal SN imaging in PeCa patients. In three consecutive PeCa patients, the fluorescent magnetic hybrid tracer (50 µl indocyanine green, 5 mg/ml, in 1 ml superparamagnetic iron oxide nanoparticles) was peritumorally injected. SNs were visualized by magnetic resonance imaging (MRI). Intra-operatively, SNs were detected using a handheld magnetometer and a fluorescence camera. Concordance was determined between MRI and magnetometer-guided SNB and between magnetic and fluorescent SN labelling. MRI revealed 29 SNs (median 4.5, range 0–8 SNs/groin). Twenty-five LNs (median 4.5, range 0–9 LNs/groin) were resected, including 16 magnetically active and 17 fluorescent SNs (median 3, range 0–6 SNs/groin, either mode). MRI and magnetometer-guided SNB had 66% concordance, magnetic and fluorescence SN labelling 96%. The diagnostic accuracy of our approach has to be evaluated in larger patient cohorts. Our radiation-free SNB technique is feasible without the need for nuclear medicine, its associated additional effort and regulations.